2012
DOI: 10.2337/dc11-1281
|View full text |Cite
|
Sign up to set email alerts
|

Age Before Stage: Insulin Resistance Rises Before the Onset of Puberty

Abstract: OBJECTIVEInsulin resistance (IR) is associated with diabetes. IR is higher during puberty in both sexes, with some studies showing the increase to be independent of changes in adiposity. Few longitudinal studies have reported on children, and it remains unclear when the rise in IR that is often attributed to puberty really begins. We sought to establish from longitudinal data its relationship to pubertal onset, and interactions with age, sex, adiposity, and IGF-1.RESEARCH DESIGN AND METHODSThe EarlyBird Diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 26 publications
11
109
1
6
Order By: Relevance
“…Our own (EarlyBird) data show no association between activity and IR in pre-adolescence (age 8 years) [10]. The higher levels of IR in the adolescent age group that we and others have reported [11][12][13] may explain the emergence of an association with physical activity around that time.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our own (EarlyBird) data show no association between activity and IR in pre-adolescence (age 8 years) [10]. The higher levels of IR in the adolescent age group that we and others have reported [11][12][13] may explain the emergence of an association with physical activity around that time.…”
Section: Introductionmentioning
confidence: 78%
“…In such circumstances, the biological control loop would be expected to oscillate spontaneously between tissue function and diminishing beta cell reserve in order to defend blood glucose [38]. These oscillations could be more closely related to age than to puberty itself, as we have suggested previously [11], explaining the link to adolescence and limited interaction with pubertal stage. The higher insulin levels in the less active children during mid-adolescence will have put a greater demand on the beta cells over that period.…”
Section: Implications Unanswered Questions and Possible Explanationsmentioning
confidence: 97%
“…Jeffery y col., observaron un incremento de insulina alrededor de los 7 años, antes del aumento de la hormona luteinizante (luteinizing hormone; LH, por sus siglas en inglés) y aparición de signos clínicos puberales. 28 El aumento de la adiposidad, de los andrógenos adrenales y del IGF-I explicarían la menor insulinosensibilidad antes del inicio puberal. Apoyando estas hipótesis, nuestro grupo de trabajo observó que la concentración de 17-hidroxiprogesterona (precursor de andrógenos) y de los niveles de IGF-I en niños sanos a edades peripuberales fueron significativamente mayores comparados con prepúberes de menor edad.…”
Section: Discussionunclassified
“…Differences during prepuberty and puberty had been previously reported. 8,[26][27][28] Based on our results, a HOMA-IR higher than 1.4, 2.0, and 2.6 in prepubertal children younger and older than 7.5 years old and pubertal children, respectively, and a G/ Ins ratio value below 10 suggest certain level of insulin resistance in children and adolescents. Our study proposes a RI for simplified glycemia and insulinemia indices obtained in fasting conditions; however, there are other indices that reflect insulin sensitivity in baseline conditions and in the post-absorption phase.…”
Section: Discussionmentioning
confidence: 99%
“…Jeffery et al observed that insulin increased around 7 years old, before the increase in luteinizing hormone (LH) and the onset of clinical signs of puberty. 28 Increases in adiposity, adrenal androgens, and IGF-1 might explain the lower insulin sensitivity observed before the onset of puberty. In support of these hypotheses, our task force observed that 17-hydroxyprogesterone (an androgen precursor) and IGF-1 levels in healthy peripubertal children were significantly higher than those in younger prepubertal children.…”
Section: Discussionmentioning
confidence: 99%